Maximizing quality in grafted tomato production systems - Jenkins, Tricia Malynn (Kansas State University, 2021)
Vegetable grafting is a unique technology that can be easily adopted by growers to improve pest and disease resistance, provide abiotic stress tolerance, and increase marketable yields. The production of grafted vegetable transplants and their use in different production systems is increasing in North America. Tomatoes (S. lycopersicum L.) are currently the most popular grafted crop. The expansion of this technology relies on the availability of high-quality grafted tomato transplants as well as the ability of grafted plants to improve production and maintain or improve fruit quality for growers. The overall objectives of this dissertation were threefold: (i) to review the literature on tomato rootstock effects on tomato fruit quality (ii) to identify quality and performance impacts of grafted tomato transplants following abiotic stress from the supply chain (iii) investigate how rootstocks can influence the yield performance and fruit quality of a high-lycopene cultivar (‘Tasti-Lee’) grown in a high tunnel. The literature review found that changes in tomato fruit quality traits from rootstocks are wide-spread and highly subject to rootstock-scion and rootstock-scion-environment interactions. However, there are numerous reports that fruit from plants grafted to vigorous rootstocks have a larger average fruit size, lower soluble solid content (SSC), lower ascorbic acid (AsA) content, and higher titratable acidity (TA). Future investigations should focus on identifying the underlying mechanisms of fruit quality changes from grafting to tomato rootstocks. For the second objective, we found that exogenous ethylene exposure reduced chlorophyll fluorescence (Fv/Fm) and caused leaf epinasty of grafted seedlings. Yet, damaged plants recovered and had similar growth parameters to the control plants three weeks after transplanting. Non-ideal transportation conditions were also assessed by exposing plants to 35 °C for 6 to 48 hours during long-distance (72-hr) transportation. Similarly, the plants experienced physiological stress as measured by Fv/Fm, but all plants survived transplanting and early growth was not impacted. In both of these experiments, grafted plants were able to better maintain Fv/Fm and reduce the severity of symptoms such as epinasty and succulent elongation compared to nongrafted plants. The results from this objective indicate that transplant quality can be negatively affected from the stress conditions tested, but early growth was not inhibited. These results also suggest that grafted plants may be able to better tolerate abiotic stress at the seedling stage compared to nongrafted plants. In regards to the third objective, a three-year high tunnel trial was conducted at the Olathe Horticulture Research and Extension Center to assess the yield and fruit quality impacts of five rootstocks grafted to the premium cultivar ‘Tasti-Lee’. Fruit quality was determined by SSC, TA, antioxidant capacity, AsA content, lycopene content, carotenoid composition, and fruit firmness. Grafting with ‘Maxifort’, ‘Fortamino’, ‘Estamino’, and ‘DRO-141-TX’ significantly increased marketable yields by 31.5%-47% above non-grafted plants. Conversely, the rootstock ‘RST-04-106-T’ did not provide any yield benefit. All of the rootstocks increased the average fruit weight by 12%. ‘RST-04-106-T’ was the only rootstock that altered fruit quality. This rootstock produced fruit with the highest SSC which was significantly higher than fruit from the rootstock ‘Maxifort.’ Moreover, ‘RST-04-106-T’ altered the relative composition of carotenoids compared to the nongrafted treatment by limiting β-carotene content in relation to the high lycopene concentrations. These results indicate that, with the proper rootstock selection, the cultivar ‘Tasti-Lee’ can be successfully integrated into high tunnel grafting systems without compromising its characteristic fruit quality attributes.
Keywords: Grafting; Rootstocks; Solanum lycopersicum; Carotenoids; Lycopene; Transplants